ChemInform Abstract: Efficient Cross‐Coupling of Dioxazaborocanes with α‐Phosphate Enamides. Issue 19 (May 2015) - Gigant, Nicolas; Honraedt, Aurelien; Gras, Emmanuel; Gillaizeau, Isabelle
Abstract: Nonaromatic α‐phosphate enamides react with heteroaromatic dioxazaborocanes to afford α‐functionalized enamides in high yields via palladium‐catalyzed cross‐coupling reactions.